Akulturasi Arsitektur Bangunan Cina pada Masjid Agung Sang Cipta Rasa Cirebon - Gunawan, Ahmad Nur Sheha; Laksitarini, Niken; Oktaviani, Aris; Aqmarina, Febrina Amalia Nur; Haran, Ikhwanuddin (UNIVERSITAS INDO GLOBAL MANDIRI, 2023)
This research explores the phenomenon of acculturation of Chinese building architecture at the Sang Cipta Rasa Grand Mosque in Cirebon, an exciting case of combining Islamic architecture and traditional Chinese elements. The main focus of this research is to understand how Architectural Chinese elements are integrated into the design of mosque buildings in a harmonious and meaningful way. This research method involves a multidisciplinary approach, including literature analysis, visual observations, and interviews with architects and local historians who have in-depth knowledge of mosques and cultural acculturation in the region. The research results reveal that Grand Mosque successfully created an architectural masterpiece that skillfully combines Chinese Architectural elements. Elements such as a curved Chinese- style roof with decorative ornaments reminiscent of Chinese culture, columns, pillars with distinctive traditional carvings, and decorative motifs on the walls illustrate the influence of Chinese architecture integrated into the mosque's design. Despite the strong Chinese influence, this building maintains the essence of Islam and local culture. This research contributes to understanding how cultural acculturation can be reflected in the physical form of buildings, especially in religious contexts. The results of this research can be a valuable reference for the planning and development of future structures that harmonize elements from different cultures while respecting the values and goals of each culture involved.